Aplikasi Metode Taguchi Untuk Menurunkan Tingkat Kecacatan Pada Produk Paving - Dian Anggraini; Shanty Kusuma Dewi; Thomy Eko Saputro (Jurnal Teknik Industri, 2015)
Home Industry Putih Jaya is a company engaged in the paving blocks manufacturing which in producing paving certainly wanst to minimize any product defects. Known types of paving product  that often occured is an easily cracked paving. An effort in the first stage to reduce the level of disability in this company is to identify the factors that affect product quality paving using fishbone diagram followed by the Taguchi method which is to determine the most influential factor and improve product quality paving so the defect rate can be  decreased. From the data calculation with the fishbone diagram, there are six factors that influential. Among the six factors, those will be identified factor has  the greatest influence resulting product quality deviates toward standards quality. Conclusion of the results showed that percentage of defect that occurs in the company initially around 4%, while by using the proposed improvement by Taguchi method decreases to 2%.  The decreasing of defect percentage of defect means that the improvement of product quality is successfully. The factors the most influential factors to  the paving is a drying process with the largest value of percent contribution in the amount of 34.5%.